1D alignment of PEDOT in a buckypaper for high-performance solid supercapacitors - Soni, Roby; Anothumakkool, Bihag; Kurungot, Sreekumar (Chemelectrochem, 2016)
A flexible solid-state supercapacitor is prepared from carbon nanotube (CNT)-based buckypaper after forming a thin layer of polyethylenedioxythiophene (PEDOT) on the surface of the CNTs in the paper. A highly conducting PEDOT phase is obtained by interfacial polymerization, in which polymerization is confined at the interface of two immiscible liquids. The hydrophilic interaction between the functionalized CNTs and the oxidizing agent (iron perchlorate, Fe(ClO4)(3)), which is located in the aqueous phase, and the restricted interaction of the oxidizing agent with the EDOT monomer in the organic layer at the immiscible interface play a vital role in establishing a uniform and aggregate-free growth pattern of PEDOT on CNT. By carefully optimizing the amount of polymer in the paper, an electrode with a sheet resistance of 3.4(-1) and equivalent series resistance of 0.95 can be prepared. A thin and flexible solid-state supercapacitor device with an overall thickness of 210m is made by using this paper as the electrodes and poly(vinyl alcohol)/lithium chloride as the gel electrolyte. The power density and energy density of the electrode are 9.94Wcm(-3) and 8.85mWhcm(-3), respectively. The device also delivers a high volumetric capacitance of 18Fcm(-3) and areal capacitance of 354mFcm(-2). The demonstrated strategy is scalable and hence the process can be conveniently applied to prepare large-area PEDOT-modified buckypapers in a short time.
Keywords: Carbon; Energy storage; nanotubes; polymerization; Supercapacitors